2007
DOI: 10.1097/qad.0b013e3282ed3cf5
|View full text |Cite
|
Sign up to set email alerts
|

Biological and behavioural impact of an adolescent sexual health intervention in Tanzania: a community-randomized trial

Abstract: The intervention substantially improved knowledge, reported attitudes and some reported sexual behaviours, especially in boys, but had no consistent impact on biological outcomes within the 3-year trial period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
371
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(383 citation statements)
references
References 31 publications
11
371
0
1
Order By: Relevance
“…However, it is of concern given that research has demonstrated that at least half of heterosexual transmission is within the context of marriage. 144 152 have been the most successful, demonstrating increases in condom use that were sustained for at least a year and, in one case, for up to three years. Kirby and his colleagues, 4 and Maticka-Tyndale and her colleagues 6,7 have drawn lessons on 'best practices' for influencing condom use from these and other studies that provide guidance for future work.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is of concern given that research has demonstrated that at least half of heterosexual transmission is within the context of marriage. 144 152 have been the most successful, demonstrating increases in condom use that were sustained for at least a year and, in one case, for up to three years. Kirby and his colleagues, 4 and Maticka-Tyndale and her colleagues 6,7 have drawn lessons on 'best practices' for influencing condom use from these and other studies that provide guidance for future work.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are similar to those of Javadnoori et al 6 , they showed that lack of proper sexual knowledge and attitude, mis-education, and inappropriate sources of sexual knowledge were the causes of young people's sexual unawareness. Unfortunately, in many cultures, parents do not feel comfortable to talk about sexual issues with their children; therefore, they are not an effective source of information and support as far as these issues are concerned, which could lead children to rely on unreliable resources 31 . Unreliable knowledge sources usually cause transfer of misconceptions and incorrect information 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Cependant, si ces mesures ont un impact certain à l'échelle de l'individu, il n'en est pas de même à l'échelle de la population [18]. En effet, à ce jour, aucune étude n'a pu montrer à cette échelle un effet de ces méthodes de prévention sur l'épidémie du VIH en Afrique, sauf en Ouganda.…”
Section: Resultsunclassified